Effect of Sharing Experiences in an Online Support Group on the Resilience of Family Caregivers of the Disabled Elderly - Abolfazl Akbari Shaker; Tayebe Pourghaznein; Jamshid Jamali; Fatemeh Esmaelzadeh (Mashhad University of Medical Sciences, 2020)
Background: Caring for a disabled elderly person causes physical and emotional problems and social isolation for family caregivers, thereby reducing their resilience. Online social networks could provide social support and effect on resilience. Aim: This study aimed to investigate the effect of sharing experiences in the online support group on the resilience of family caregivers of the disabled elderly. Method: This randomized clinical trial was conducted on 58 family caregivers of the disabled elderly in Mashhad, Iran. The participants were selected using convenience sampling and assigned to intervention and control groups using the permuted-block randomization technique. The participants in the intervention group shared their experiences of the problems faced by them due to caring for the disabled elderly for six weeks in an online support group with other caregivers. The data were collected using a demographic characteristics form, the World Health Organization Disability Assessment Schedule, and the Connor-Davidson Resilience Scale before and after the intervention. Finally, the data were analyzed in SPSS software (version 24). Results: The participants in the intervention group reported a significantly higher level of resilience at the end of the intervention, compared to the control group (P˂0.05). Implications for Practice: The creation of an online support group for caregivers is a low-cost measure and does not require advanced clinical facilities. Furthermore, nurses can implement interventions to improve caregivers' resilience. Moreover, an increase in resilience can improve caregiving abilities while caring for disabled elderly.